Glucose Ingestion Does Not Improve Maximal Isokinetic Force. (January 2016) - Fairchild, Timothy J.; Dillon, Paul; Curtis, Caroline; Dempsey, Alasdair R.
Abstract : Abstract: Fairchild, TJ, Dillon, P, Curtis, C, and Dempsey, AR. Glucose ingestion does not improve maximal isokinetic force. J Strength Cond Res 30(1): 194–199, 2016—The purpose of this study was to assess maximal isokinetic leg extension force in response to glucose ingestion and to determine whether any performance changes occur in a time-dependent manner. Seventeen young (22.1 ± 3.9 years), lean (%body fat [%BF]: 14.3 ± 8.0; %BF males: 9.7 ± 4.2; %BF females: 23.7 ± 4.2), and recreationally active (>150 min·wk −1 of physical activity) male ( n = 11) and female participants completed the trials. Using a double-blinded crossover design, participants performed sets of 3 maximum isokinetic efforts on a dynamometer (HumacNorm) before and after (5, 15, 30, 45, 60, 75, and 90 minutes after) ingesting either a carbohydrate (75 g glucose) or isovolumic placebo (saccharin-flavored) drink. Blood glucose and electromyography (EMG) were recorded concurrent with force output (max peak force; mean peak force). Despite a significant rise in blood glucose (mean glycemic excursion = 4.01 ± 1.18 mmol·L −1 ), there were no significant interactions in any (absolute or percentage) force (mean peak force: p ≥ 0.683; max peak force: p ≥ 0.567) or EMG (mean peak EMG: p ≥ 0.119; max peak EMG: p ≥ 0.247) parameters measured. The ingestion of glucose resulted in a 3.4% reduction in mean force across subsequent time points (highest: +2.1% at 15 minutes; lowest: −8.6% at 90 minutes after ingestion); however, this effect was small ( d < 0.1). The ingestion of glucose does not alter performance of maximal isokinetic efforts in recreationally active young individuals. Additionally, there were no differences in force when assessed as a function of time after glucose ingestion. Consequently, in the absence of fatigue, carbohydrate ingestion is unlikely to present any ergogenic benefits to athletes performing resistance-based exercise.